Environmental cost control system of manufacturing enterprises using artificial intelligence based on value chain of circular economy - Chen, Min; Liu, Qian; Huang, Shuai; Dang, Chenlu (Enterprise information systems, 2022)
In this study, expecting to form a virtuous circle conducive to socio-economic development. The problems of environmental cost control mode, and the relationship between the value chain and environmental cost control was discussed. The decision tree algorithm of artificial intelligence (AI) was applied in designing the environmental cost control system of manufacturing enterprises to realise the internalisation of environmental cost. The external environmental consumption cost was calculated by taking an oil production plant as the research object according to the environmental cost report of the oil production plant, and relevant suggestions were proposed for the enterprise's environmental cost scheme control.